The Transmittance, Transmittance Wavefront, and Laser Induced Damage Properties of Thin Fluoride Polymer Films May Be Used as Short Pulse Laser Debris Shields. (12th May 2016) - Chen, Shufan; Huang, Chuanqun; Jiang, Xiaodong; Luo, Xuan; Fang, Yu; Wu, Weidong
Abstract : Debris mitigation which pollutes and even damages the optical elements is a major challenge for all high-peak-power lasers system. In order to solve the problem, we employed some preliminary research. In this work, first, the film optical properties of fluorinated ethylene propylene (FEP), perfluoroalkoxy copolymer (PFA), and ethane-tetrafluoroethylene copolymer (ETFE) were investigated with respect to their possible application as laser debris shields. The results indicate that three of the polymer films have high transmittance at 355 nm, especially in FEP film, the transmittance of which at 355 nm is near to 94%. The transmittance wavefront and the laser that induce damage of FEP film were investigated further. The result indicates that the wavefront error of FEP film (with a diameter of 90 mm) is about 0.33 λ . The damage test was performed by a 355 nm neodymium:yttrium aluminum garnet (Nd:YAG) laser with a 9.3 ns pulse duration, and it was found that the highest nondamage fluence for FEP film is 10.35 J/cm 2 . Through a demonstration experiment, it was testified that the FEP film can prevent large amount of metal fractions and the FEP film can be used as the debris shields indeed.